Arsenic trioxide induces regulatory functions of plasmacytoid dendritic cells through interferon-α inhibition - Yishan Ye; Laure Ricard; Lama Siblany; Nicolas Stocker; Frédéric De Vassoigne; Eolia Brissot; Baptiste Lamarthée; Arsène Mekinian; Mohamad Mohty; Béatrice Gaugler; Florent Malard (Elsevier, 2020)
Arsenic trioxide (As2O3) is recently found to have therapeutic potential in systemic sclerosis (SSc), a life-threatening multi-system fibrosing autoimmune disease with type I interferon (IFN-I) signature. Chronically activated plasmacytoid dendritic cells (pDCs) are responsible for IFN-I secretion and are closely related with fibrosis establishment in SSc. In this study, we showed that high concentrations of As2O3 induced apoptosis of pDCs via mitochondrial pathway with increased BAX/BCL-2 ratio, while independent of reactive oxygen species generation. Notably, at clinical relevant concentrations, As2O3 preferentially inhibited IFN-α secretion as compared to other cytokines such as TNF-α, probably due to potent down-regulation of the total protein and mRNA expression, as well as phosphorylation of the interferon regulatory factor 7 (IRF7). In addition, As2O3 induced a suppressive phenotype, and in combination with cytokine inhibition, it down-regulated pDCs' capacity to induce CD4+ T cell proliferation, Th1/Th22 polarization, and B cell differentiation towards plasmablasts. Moreover, chronically activated pDCs from SSc patients were not resistant to the selective IFN-α inhibition, and regulatory phenotype induced by As2O3. Collectively, our data suggest that As2O3 could target pDCs and exert its treatment efficacy in SSc, and more autoimmune disorders with IFN-I signature.